2009
DOI: 10.2503/jjshs1.78.169
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on Berry Composition of Interspecific Hybrid Wine Grape ‘Kadainou R-1’ (Vitis ficifolia var. ganebu × V. vinifera ‘Muscat of Alexandria’)

Abstract: High temperature affects berry composition, especially titratable acidity, total soluble solids, and anthocyanin content. Vitis ficifolia var. ganebu, a wild grape of sub-tropical origin with a low chilling trait, develops good coloration in its natural habitat, where daytime and nighttime temperatures are high during the berry ripening stage, while V. vinifera 'Muscat of Alexandria', a table grape, has large berries and high sugar content, hence, it was hypothesized that hybridizing V. ficifolia var. genebu w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 27 publications
6
34
0
Order By: Relevance
“…The results are in agreement with a number of researchers studying composition of the cloudberry/ bakeapple fruit (Faragher 1983;Poudel et al 2009;Akerstrom et al 2010;Martinussen et al 2010;Zheng et al 2012;Li 2013).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results are in agreement with a number of researchers studying composition of the cloudberry/ bakeapple fruit (Faragher 1983;Poudel et al 2009;Akerstrom et al 2010;Martinussen et al 2010;Zheng et al 2012;Li 2013).…”
Section: Discussionsupporting
confidence: 82%
“…In our study, fruits collected from all three locations in 2012 had a significantly higher total soluble solids content (9.5%) than in 2011 (9.0%) and almost double of that reported by Viljakainen et al (2002) in studies (5.3%) on fruit from Finland. According to research done by Poudel et al (2009), the higher temperature would result in decreasing of accumulation rates of sugars (glucose and fructose). On the other hand, research indicated that total sugar contents in sea buckthorn berries grown at higher latitude were lower than those grown at lower latitude (Zheng et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The high temperature limit for many metabolic processes in grapevine was found to be at 30 • C (Coombe, 1987). In their studies, Poudel et al (2009) also revealed 25 • C as the optimum temperature for phenolic/flavonol accumulation in 'Kadainou-R1' grapes, above or below which there was a reduction in their synthesis or accumulation. Cluster shading resulted in a substantial reduction in accumulation of flavonols and skin proanthocyanidins and minimal differences in anthocyanins in 'Pinot Noir' grapes (Cortell and Kennedy, 2006).…”
Section: Discussionmentioning
confidence: 93%
“…Experiments with an artificial temperature treatment indicated that grape berries also cannot develop their color at a too-low temperature (Coombe, 1987;Kobayashi et al, 1965;Poudel et al, 2009). The skin color rating had no significant correlation with temperature at <24°C (the open circles in Fig.…”
Section: Comparison Of Skin Color Levels Of the Three Cultivarsmentioning
confidence: 99%